Hydrogen sulfide alleviates uremic cardiomyopathy by regulating PI3K/PKB/mTOR-mediated overactive autophagy in 5/6 nephrectomy mice - Feng, Jianan; Li, Han; Wang, Shixiang (Frontiers in Pharmacology, 2022)
The gasotransmitter hydrogen sulfide (H2S) plays important physiological and pathological roles in the cardiovascular system. However, the involvement of H2S in recovery from uremic cardiomyopathy (UCM) remains unclear. This study aimed to determine the therapeutic efficacy and elucidate the underlying mechanisms of H2S in UCM. A UCM model was established by 5/6 nephrectomy in 10-week-old C57BL/6 mice. Mice were treated with sodium hydrosulfide (NaHS, H2S donor), L-cysteine [L-Cys, cystathionine gamma-lyase (CSE) substrate], and propargylglycine (PPG, CSE inhibitor). Treatment of H9C2 cardiomyocytes utilized different concentrations of uremic serum, NaHS, PPG, and PI3K inhibitors (LY294002). Mouse heart function was assessed by echocardiography. Pathological changes in mouse myocardial tissue were identified using hematoxylin and eosin and Masson’s trichrome staining. Cell viability was assessed using the Cell Counting Kit-8. The protein expressions of CSE, p-PI3K, PI3K, p-PKB, PKB, p-mTOR, mTOR, and autophagy-related markers (Beclin-1, P62, and LC3) were detected using Western blotting. We found that NaHS and L-Cys treatment attenuated myocardial disarray, fibrosis, and left ventricular dysfunction in UCM mice. These abnormalities were further aggravated by PPG supplementation. Enhanced autophagy and decreased phosphorylation of PI3K, PKB, and mTOR protein expression by UCM were altered by NaHS and L-Cys treatment. In vitro, uremic serum increased overactive autophagy and decreased the phosphorylation levels of PI3K, PKB, and mTOR in cardiomyocytes, which was substantially exacerbated by endogenous H2S deficiency and attenuated by pre-treatment with 100 µm NaHS. However, the protective effects of NaHS were completely inhibited by LY294002. These findings support a protective effect of H2S exerted against UCM by reducing overactive autophagy through activation of the PI3K/PKB/mTOR pathway.